1990
DOI: 10.1507/endocrj1954.37.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LH-RH on the Release of Sulfated Lutropin: A Potential In Vitro Bioassay for LH-RH.

Abstract: Sheep pituitary cells prelabelled with radioactive [35S] sulfate (35SO4(2-)) were incubated with different concentrations of LH-RH and the release of LH (lutropin) into the medium was monitored in terms of immunoprecipitable [35S] sulfated LH radioactivity and estimation of LH in the same sample by radioimmunoassay. A dose dependent response was obtained with a maximum of a 16 fold increase in immunoprecipitable 35SO4(2-) -labelled LH radioactivity in the medium which was confirmed by radioimmunoassay. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Sulfation of LH has been proposed to act as a sorting signal (Pierce & Parsons, 1981, Kohli & Muralidhar, 1990, Boime et al , 1999, Bousfield George R. et al , 2006). Kohli and Muralidhar (1990) compared the LH-RH response of LH by indirect double labeling experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfation of LH has been proposed to act as a sorting signal (Pierce & Parsons, 1981, Kohli & Muralidhar, 1990, Boime et al , 1999, Bousfield George R. et al , 2006). Kohli and Muralidhar (1990) compared the LH-RH response of LH by indirect double labeling experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Kohli and Muralidhar (1990) compared the LH-RH response of LH by indirect double labeling experiments. From these data they suggested that sulfate could be a sorting signal for LH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation